Reciprocal inhibition of NOTCH and SOX2 shapes tumor cell plasticity and therapeutic escape in triple-negative breast cancer - Morgane Fournier; Joaquim Javary; Vincent Roh; Nadine Fournier; Freddy Radtke (EMBO Molecular Medicine)
Abstract Cancer cell plasticity contributes significantly to the failure of chemo- and targeted therapies in triple-negative breast cancer (TNBC). Molecular mechanisms of therapy-induced tumor cell plasticity and associated resistance are largely unknown. Using a genome-wide CRISPR-Cas9 screen, we investigated escape mechanisms of NOTCH-driven TNBC treated with a gamma-secretase inhibitor (GSI) and identified SOX2 as a target of resistance to Notch inhibition. We describe a novel reciprocal inhibitory feedback mechanism between Notch signaling and SOX2. Specifically, Notch signaling inhibits SOX2 expression through its target genes of the HEY family, and SOX2 inhibits Notch signaling through direct interaction with RBPJ. This mechanism shapes divergent cell states with NOTCH positive TNBC being more epithelial-like, while SOX2 expression correlates with epithelial-mesenchymal transition, induces cancer stem cell features and GSI resistance. To counteract monotherapy-induced tumor relapse, we assessed GSI-paclitaxel and dasatinib-paclitaxel combination treatments in NOTCH inhibitor-sensitive and -resistant TNBC xenotransplants, respectively. These distinct preventive combinations and second-line treatment option dependent on NOTCH1 and SOX2 expression in TNBC are able to induce tumor growth control and reduce metastatic burden.